Seventh Working IEEE/IFIP Conference on Software Architecture (WICSA 2008) 2008
DOI: 10.1109/wicsa.2008.9
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Recovery Style for Modeling and Analyzing System Recovery

Abstract: An analysis of the existing approaches for representing architectural views reveals that they focus mainly on functional concerns and are limited when considering quality concerns. We introduce the recovery style for modeling the structure of the system related to the recovery concern. The recovery style is a specialization of the module viewtype in the Views&Beyond approach. It is used to communicate and analyze architectural design decisions and to support detailed design with respect to recovery. We illustr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…We use a UML profile for both SA and FT [20,25] and made necessary extensions to specify FTSs and FTSAs. There are three kinds of components in this UML profile: «NFTUnit», «FTUnit» and «FTFaci» components.…”
Section: Modeling Solutions As Fault-tolerant Stylesmentioning
confidence: 99%
See 2 more Smart Citations
“…We use a UML profile for both SA and FT [20,25] and made necessary extensions to specify FTSs and FTSAs. There are three kinds of components in this UML profile: «NFTUnit», «FTUnit» and «FTFaci» components.…”
Section: Modeling Solutions As Fault-tolerant Stylesmentioning
confidence: 99%
“…Previous work in the area mainly focuses on how to model a specific fault-tolerant mechanism [10,13,14,25,26], for example, exception handling-based mechanism [14,26]. A few studies consider the reasoning or analysis on an FTS.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…-Project planning: Practitioners need to construct 'To be' execution models to support two particular activities. On the one hand, these models are needed to distinguish and analyze the difference between considered alternative or future architectures and designs that aim to improve quality attributes such as reliability (Sozer and Tekinerdogan, 2008), dependability, and safety (Hunt et al, 2007). This is important, as it is often not obvious how the realization of the alternative design may affect the structure and behavior of the system at runtime, and therefore influence other system quality attributes.…”
Section: Organization Concerns Related To System Evolvabilitymentioning
confidence: 99%
“…As part of our research on the evolvability of large softwareintensive systems (van de Laar et al, 2007), we observed that suitable architectural views are indispensable assets to improve and sustain the evolvability of systems (Muller, 2004(Muller, , 2009. Such views help practitioners to understand the existing system, to plan and evaluate intended changes, and to communicate them to others efficiently.…”
Section: Introductionmentioning
confidence: 99%